Design of Group Investigation (GI) Learning Model assisted by animation media to social skills in social studies learning - Husna, Husna; Iskandar, Iskandar; Herlina, Herlina (PT. Riset Press International, 2024)
Education is an important capital​ For advance A nation Because prosperity and progress A nation can seen from level his education. Education holds role important in create individual quality. Education requires appropriate innovations​ with progress knowledge knowledge and technology without ignore values humanity. Formulation problem How application of the Group Investigation learning model, How use of animation media on the eyes social studies lessons in class V, How Skills social students in social studies subjects in class V, Why Skills social become interesting use design a form of Group Investigation (GI) learning model assisted by animation media in social studies learning in class V at SDN Atananga. Research objectives, Analyze design a form of Group Investigation (GI) learning model assisted by animation media to social skills in social studies learning in class V of SDN Tananga. Research methods used by researchers​ namely research methods qualitative Study qualitative addressed For understand phenomenon social perspective participants which are the people invited interviewed, observed, asked provide data, opinions, thoughts, perceptions. Animation media research results learning is a medium that contains gathering created image​ like that appearance so that produce movement and equipped with interesting audio as well as contain values learning. With use proper animation, material​ difficult learning​ or abstract can be delivered with way more​ easy understood by students. Animation is also possible present information in a way interactive, possible student participate active in the learning process.